Revitalisasi Pendidikan Karakter melalui Islamisasi Kampus di Universitas Muhammadiyah Sukabumi - Idharoelhaq, Andri Moewashi; Aziz, Muhammad Thariq (Universitas Islam Negeri Raden Intan Lampung, 2018)
Campus Islamization has been held at Muhammadiyah University Sukabumi since 2014 but its effectiveness has not been measured especially to revitalize student character education. This research is a descriptive study with a quantitative approach. The instruments used included observation sheets for student activities in the classroom and campus environment. The results of the research show that the highest character is discipline (93.3%) and the lowest is the national spirit (60%) and the highest character is hard work (84%) and the lowest is fond of reading (61%). So it can be concluded that the results of the study show character that is expected to become complete information about the implementation of Islamization on campus as a form of efforts to revitalize character education especially at the University of Muhammadiyah Sukabumi.